1994
DOI: 10.1042/bj2990437
|View full text |Cite
|
Sign up to set email alerts
|

Biodistributions of air-filled albumin microspheres in rats and pigs

Abstract: The air-filled microspheres of the ultrasound-contrast agent Albunex are unique in that the walls consist of human serum albumin molecules which have been made insoluble by sonication of the albumin solution. The microspheres were isolated by flotation, and the washed microspheres were labelled with 125I. The labelled material was cleared from the circulation mainly as particles, not as soluble albumin molecules. In rats, 80% of intravenously injected microspheres were cleared from the blood within 2 min. Near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 19 publications
6
48
0
Order By: Relevance
“…In the liver, targeted MBs were found in Kupffer cells as early as 4 minutes after administration. This finding is consistent with that in a study by Walday et al (10).…”
Section: Molecular Imaging: Tumor Angiogenesis Assessment With Microbsupporting
confidence: 83%
See 3 more Smart Citations
“…In the liver, targeted MBs were found in Kupffer cells as early as 4 minutes after administration. This finding is consistent with that in a study by Walday et al (10).…”
Section: Molecular Imaging: Tumor Angiogenesis Assessment With Microbsupporting
confidence: 83%
“…Walday et al (10) used traditional ex vivo biodistribution techniques to study the organ distribution of first-generation, nontargeted air-filled iodine 125-labeled albumin microspheres (Albunex) in both rats and pigs up to 90 minutes after intravenous administration. Three minutes after administration in rats, about 60% of the radiolabeled albumin microspheres were recovered in the liver, 9% of them were recovered in the spleen, and 5% of them were recovered in the lungs, with only small amounts in other organs such as the brain, heart, and kidneys (10). In contrast, in pigs, more than 90% of the albumin microspheres were recovered in the lungs, most likely because of the presence of intravascular macrophages in the porcine lungs (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that the volume of ethanol can be substantially reduced to 0.8 mL (compared with 40 mL, as published previously [22,23]), which caused moderate-to-severe TNBS-mediated inflammation with minimal discomfort to the animals. Another detail worth noting is the need to premedicate pigs with aspirin, indomethacin, or a specific thromboxane receptor blocker before injecting lipid-based particles such as MBs (16)(17)(18), because pigs have abundant intrapulmonary macrophages (26,27). These macrophages rapidly clear intravenously injected particles and immediately release substances such as vasoconstrictor thromboxane A2, with subsequent pulmonary arterial hypertension, systemic…”
Section: Discussionmentioning
confidence: 99%